Financing of sports clubs from the budget of local self-government units – ways to support and the study the interpretation of regulations - Jakub Rzeszowski (Prawo Budżetowe Państwa i Samorządu)
The article characterises alternative methods of financing sports clubs. The text also presents the concept of a sports club as well as legal and organizational forms. The possibilities of raising funds were also discussed. The article highlights an importance of resources obtained by sports clubs from budgets of local self-government units. The summary concludes that sports clubs play a significant role and that without an appropriate financial support from local government units, the activities of these clubs would be constricted.